Pregnancy outcomes of PCOS overweight/obese patients after controlled ovarian stimulation with the GnRH antagonist protocol and frozen embryo transfer - Rui Chen; Shiping Chen; Manting Liu; Hua He; Haiyan Xu; Hanyan Liu; Hongzi Du; Weihua Wang; Xuefeng Xia; Jianqiao Liu (BMC, 2018)
Abstract Background Overweight/obese women with polycystic ovary syndrome (PCOS) are at increased risk of subfertility and complications of pregnancy, compared with normal-weight women. To implement controlled ovarian hyperstimulation (COH), the improved efficacy of the gonadotrophin-releasing hormone antagonist (GnRH-ant) protocol has been demonstrated, as well as frozen embryo transfer (FET). Objective This retrospective study evaluated the pregnancy outcomes after combined GnRH-ant protocol and FET in overweight/obese women with PCOS, with reference to that of normal-weight women with PCOS. Methods Women with PCOS (n = 398) who underwent the GnRH-ant protocol for COH followed by FET, were stratified as normal-weight (BMI < 24 kg/m2) or overweight/obese (BMI ≥24 kg/m2). The outcomes of pregnancy were compared. Results The overweight/obese patients had significantly lower rates of embryo implantation (47.7%), live birth (47.8%), and live births of twins (10.9%) compared with the normal-weight group (58.4%, 60.8%, and 30.0%, respectively; P = 0.006, 0.015, and 0.000), while the rate of late abortion was significantly higher (11.0% cf. 3.8%, P = 0.030). BMI was the only significant factor affecting the probability of live birth. Conclusion The pregnancy outcomes of overweight/obese women with PCOS after COH via the GnRH-ant protocol and FET remained at a significant deficit compared with that of normal-weight women with PCOS.